A review of fatigue behavior of FRP composites. (2022) - Arora, Shrey; Chitkara, Rupesh; Dhangar, Ayush Singh; Dubey, Divyanshu; Kumar, Ranjeet; Gupta, Anurag
Abstract: The Fiber Reinforced Plastic (FRP) composite may be defined as a combination of two or more materials that individually might lack but together shows desirable properties. FRP composites are lightweight, corrosion-resistant, impact-resistant, electrically insulated, low-maintenance, less expensive, resistant to moisture, termites, fungus, and bacterial development and services for extended periods of time. Public works (federal, state, and municipal parks), automobiles, aerospace, wood replacement, benches, boardwalks, decks, fences, playgrounds, ramps, military, construction, flooring, siding, roofing, and restrooms are just a few of its applications. The fatigue behaviour test is the crucial test that traditional material and composite materials must pass through. It is the method of assessing materials for their cyclic behaviour usually at a constant rate, thus a material's endurance limit can only be discovered through fatigue testing. FRP composite manufactured through different processes into various final products were evaluated under a cyclic load till they reached their failure or till they reached a percentage of overall stiffness loss to determine its fatigue behaviour. This review paper sums up the changes in the fatigue behaviour obtained on FRP composites of the various composition prepared through different operations in different matrices and fillers.